Design de produto - Neurociência: contribuições às metodologias projetuais aplicadas ao design automotivo - Rosa, Carolina Vieira Liberatti (2019)
Currently, the design methodologies applied to Product Design indicate a limitation to the measurement of users' emotional responses, specifically in terms of correlating such responses to the definition of relevant product design requirements. The project methodologies access the emotional response of the outsourced user verbally, through semantic associations, or expressed in self-evaluation questionnaires. Neuroscience enables access to automatic internal changes of the individual's body state, and can bring clarification about their processes of cognition, perception and behavior. This dissertation is based on the mapping of the current design methodologies applied to Automotive Design and the techniques of neurophysiological assessment, to discuss the user's complex emotional processing mechanism, involved in the perception and evaluation of design elements. Among the contributions derived from the Product Design and Neuroscience cooperation, and supported by this dissertation in the scope of Automotive Design, we highlight: (a) anticipation of emotional and behavioral reactions by mapping patterns; (b) identification of wishes and/or corresponded expectations or not; (c) project orientation regarding consistent and affective interactions between user and product; (d) reducing the discrepancy between the user's emotional response and the intentional concept of the project; (e) viability to 'access' brain areas related to visual memory and, thereby, provide information relevant to the perception of the product; (f) measurement of the degree of complexity and impacts to the brain of the stimuli coming from the products; (g) unveiling the brain mechanisms involved in the process of distinguishing between design alternatives of a product; (h) evaluation of the neurophysiological behavior of the user in the processes of preference and decision making, resulting from the choice among products; (i) identification of design requirements demanded by the human organism itself.